Analisis Brand equity Produk Fashion Hijab Merek Elzatta - Widiyanti, Wiwik (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2021)
Brand equity in reality illustrates the value of a brand from consumer perceptions and experiences of the brand. There are four main categories that make up brand equity, namely brand awareness, brand association, perceived quality, and brand loyalty. Brand equity is used to determine the marketing strategy that a company will carry out. Therefore research is needed to collect data and analyze it. This research on Brand equity in Elzatta's hijab fashion product aims to analyze the elements of Brand equity so that it is expected to contribute data to create a marketing strategy for the brand. The results showed that brand awareness was really at the top of mind. Meanwhile, the three impressions of the Elzatta brand association are quality fabric, good design / design and providing comfort to the wearer. The brand quality felt by Elzatta shows that most of the attributes of Elzatta's hijab fashion products have achieved high performance. Only for the attributes of the thickness of the material and the price it is necessary to increase and improve its performance. On brand loyalty, Elzatta obtained data on consumers who buy because the price is more than consumers who buy out of habit. This is an accident that consumers will switch brands from rising prices. As for consumers who buy because satisfaction is the most, this of course will affect consumer loyalty